Learning exchange: a collaborative work between course units - Silva, Flora (2021)
The joint reflection between teachers from different areas, and with different backgrounds, on the strategies to be implemented in some course units, with the aim of building a scenario that fosters learning and, in parallel, allows the development of transversal skills, led to the idealization of a teaching proposal in which, in addition to valuing learning in a real work context, it was intended to promote the exchange of knowledge acquired by the students from different course units. The proposal in question involved the course units of Mechanical Technology I and Manufacturing Processes I, of the 2nd year of the Bachelor in Mechanical Engineering and in Technology and Industrial Management, respectively, and the course unit of Safety and Environment of the 1th year of the Higher Professional Technical Course in Mechanical Technology and Vehicles. Summing up, in addition to two study visits to companies in the field of metallomechanics, there was an exchange of knowledge between students. In this context, undergraduate students were given the role of conducting communication sessions that would clarify some of the mechanical processes observed in companies. Similarly, to the students of the Higher Professional Technical Course were tasked with sharing about the hazards and risks inherent in the real work context in the visited companies and the respective awareness of the means of protection to be used. The analysis and evaluation of the experience carried out was based on the observations of the teachers of the classes, in the productions developed by the students, in the intermediate questionnaires that were carried out after the visits, more directed to the expectations and learning carried out and, in a final questionnaire, in which students were asked for their opinion on various aspects related to the developed experience. In this sense, in addition to describing the project carried out, it is intended to focus on some of the opinions/perceptions of teachers and students involved about the contribution of the experience to the promotion of learning.